POTATO MINITUBER PRODUCTION BY AEROPONICS: EFFECTS OF GENOTYPE AND PLANT ORIGIN - Oljača, Jasmina; Broćić, Zoran; Pantelić, Danijel; Rudić, Jelena; Poštić, Dobrivoj; Momčilović, Ivana (Journal of Agricultural Sciences (Belgrade), 2024)
Aeroponics is a modern farming technology for growing potatoes without soil, enabling the efficient production of high-quality pre-basic seed potatoes (minitubers). In this system, the roots and underground stems (stolons) of the potato plants grow within closed modules, suspended in a fine mist of a nutrient-rich solution that continuously recirculates. This setup enables the formation of numerous minitubers with a length greater than 10 mm during the growing period. Our study aimed to evaluate the impact of genotype and planting material origin on minituber production in an aeroponic facility in Guča, Serbia. Three potato cultivars were analyzed: Cleopatra, Kennebec, and Désirée, using two types of planting material: acclimated microplants and plants derived from the previous season’s minitubers. The plants were cultivated aeroponically from late May to December 2019, with a planting density of 24 plants per square meter and harvest intervals of approximately 14 days. The cultivar Désirée produced the highest average number of minitubers per plant (19.89), followed by Kennebec (15.71) and Cleopatra (11.05). The average weight of minitubers was significantly greater in plants grown from last season’s minitubers compared to plants of in vitro origins. The Kennebec plants originating from minitubers achieved the highest yield of 10.27 kg per square meter. Additionally, plants originating from minitubers consistently produced tubers throughout the entire cultivation period in the aeroponic growing system.